The Application of the Rebus Sic Stantibus Principle in Oil Sales and Purchase Agreements by PT Pertamina (Persero) Amidst Geopolitical Instability in the Middle East - Budi Constantin Sihombing; Roida Nababan; Samuel Situmorang (Journal of Legal and Cultural Analytics, 2026)
Geopolitical instability in the Middle East—triggered by armed conflict, economic sanctions, disruptions to energy distribution routes, and global oil price fluctuations—has brought about significant changes in the execution of international crude oil sales contracts. These conditions potentially affect the ability of the parties involved, including PT Pertamina (Persero), to fulfill their agreed-upon contractual obligations. This study aims to analyze whether geopolitical instability in the Middle East can be classified as a "fundamental change of circumstances" that meets the criteria for invoking the rebus sic stantibus principle, and to examine the legal implications and dispute resolution mechanisms should this principle be applied to oil sales agreements involving PT Pertamina (Persero). The study employs a normative legal research method utilizing statutory, conceptual, and case-based approaches. Legal materials—comprising primary, secondary, and tertiary sources—were analyzed qualitatively using a descriptive-analytical method. The findings indicate that, under certain conditions, geopolitical instability in the Middle East can be categorized as a fundamental change of circumstances if it meets the elements recognized under the rebus sic stantibus doctrine: namely, a change that was unforeseeable at the time the contract was concluded, occurred beyond the parties' control, significantly altered the contract's economic balance, and rendered performance excessively burdensome without making it impossible to execute.